Urban Agriculture, Sustainability, and Internet-of-Things : Applying UTAUT to Determine the Behavioural Intention to Use IoT - Prinsloo, Tania (University of Pretoria, 2023)
Thesis (MIT (Information Systems))--University of Pretoria, 2022.